Differential sensitivity of metabolic pathways in sugar beet roots to combined salt, heat, and light stress - García-Caparrós, Pedro; Vogelsang, Lara; Persicke, Marcus; Wirtz, Markus; Kumar, Vijay; Dietz, Karl-Josef (Physiologia plantarum, 2022)
Plants in nature commonly encounter combined stress scenarios. The response to combined stressors is often unpredictable from the response to single stresses. To address stress interference in roots, we applied salinity, heat, and high light to hydroponically grown sugar beet. Two main patterns of metabolomic acclimation were apparent. High salt of 300 mM NaCl considerably lowered metabolite amounts, for example, those of most amino acids, γ-amino butyric acid (GABA), and glucose. Very few metabolites revealed the opposite trend with increased contents at high salts, mostly organic acids such as citric acid and isocitric acid, but also tryptophan, tyrosine, and the compatible solute proline. High temperature (31°C vs. 21°C) also frequently lowered root metabolite pools. The individual effects of salinity and heat were superimposed under combined stress. Under high light and high salt conditions, there was a significant decline in root chloride, mannitol, ribulose 5-P, cysteine, and l-aspartate contents. The results reveal the complex interaction pattern of environmental parameters and urge researchers to elaborate in much more detail and width on combinatorial stress effects to bridge work under controlled growth conditions to growth in nature, and also to better understand acclimation to the consequences of climate change.